1981
DOI: 10.1007/bf00251349
|View full text |Cite
|
Sign up to set email alerts
|

Scintigraphic image contrast-enhancement techniques: Global and local area histogram equalization

Abstract: This article develops two contrast-modification techniques for the display of scintigraphic images. Based on histogram-modification techniques, histogram equalization, where each level of gray is used to the same extent, gives maximum entropy. The first technique uses the application of histogram equalization in the whole image. To eliminate contrast attenuation small but important portion of the gray scale histogram, local area histogram equalization has been applied to images with differences in intensity. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Many proven contrast-enhancement methods have been described in the literature, but their use in bone scintigraphy has not been investigated (4,5). Studies to improve the quality of bone scintigraphy images have been previously published (6)(7)(8). Verdenet et al (6) used a global histogram equalization technique to enhance bone scintigraphy images.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many proven contrast-enhancement methods have been described in the literature, but their use in bone scintigraphy has not been investigated (4,5). Studies to improve the quality of bone scintigraphy images have been previously published (6)(7)(8). Verdenet et al (6) used a global histogram equalization technique to enhance bone scintigraphy images.…”
Section: Discussionmentioning
confidence: 99%
“…Studies to improve the quality of bone scintigraphy images have been previously published (6)(7)(8). Verdenet et al (6) used a global histogram equalization technique to enhance bone scintigraphy images. They found that the technique improves the readability of the images.…”
Section: Discussionmentioning
confidence: 99%
“…Such output images may produce false-positive results in some cases if the reporting is made solely based on histogram equalization followed by contrast stretch and the normalization as authors have mentioned in the study. [ 9 ] Since this was a retrospective study, number of false-positive results were not considered or investigated in this study. This technique can be applied on low contrast studies and can be, especially, useful if one is not interested in looking for contrast between bone tissue uptakes and is only interested in looking for the presence of a lesion.…”
Section: Discussionmentioning
confidence: 99%
“…have used GHE technique for the enhancement of bone scintigraphic images. [ 9 ] They found that the technique improves the readability of data and is suitable to bone scintigraphy. However, they have also mentioned observation of few false positive results as application of this technique.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, pupil removal is left for this step to be performed; with only iris and pupil, the contrast enhancement method would yield better performance (Verdenet, Cardot et al 1981). As shown in Figure 4.13, image (a) is the outcome from the previous step (outer iris and upper and lower eyelid boundary delineation).…”
Section: Pupil Eyelash Detection and Results Reliability Verificationmentioning
confidence: 99%